(untitled) (Research, Society and Development, 2020)
This research consists of a case study that aimed to investigate the occurrence of meaningful learning in a group formed by 40 students of integrated technical education at the Federal Institute of Minas Gerais, São João Evangelista, who participated in a course on basic concepts of astronomy. The theoretical framework adopted for the research was David Ausubel’s theory of meaningful learning and the main instrument for data collection was the questionnaire, applied as pre and post-test. The data obtained were submitted to qualitative and quantitative analyses, obtaining, as results, confirmation of the occurrence of meaningful learning through the application of the Student’s t-test. It was concluded that this type of course can be a viable alternative for the teaching of astronomy in this institution and that the reference material is adequate, but requires adjustments by the teacher, in order to achieve the proposed objectives.